Beneficial non-anticoagulant mechanisms underlying heparin treatment of COVID-19 patients (2020)
Coronavirus disease-2019 (COVID-19) is associated with severe inflammation in mainly the lung, and kidney. Reports suggest a beneficial effect of the use of heparin/low molecular weight heparin (LMWH) on mortality in COVID-19. In part, this beneficial effect could be explained by the anticoagulant properties of heparin/ LMWH. Here, we summarise potential beneficial, non-anticoagulant mechanisms underlying treatment of COVID-19 patients with heparin/LMWH, which include: (i) Inhibition of heparanase activity, responsible for endothelial leakage; (ii) Neutralisation of chemokines, and cytokines; (iii) Interference with leukocyte trafficking; (iv) Reducing viral cellular entry, and (v) Neutralisation of extracellular cytotoxic histones. Considering the multiple inflammatory and pathogenic mechanisms targeted by heparin/LMWH, it is warranted to conduct clinical studies that evaluate therapeutic doses of heparin/LMWH in COVID-19 patients. In addition, identification of specific heparin-derived sequences that are functional in targeting non-anticoagulant mechanisms may have even higher therapeutic potential for COVID-19 patients, and patients suffering from other inflammatory diseases.